EFEKTIFITAS SISTEM INFORMASI MANAJEMEN ASET PADA LEMBAGA PENDIDIKAN KEJURUAN - Fahmi Poernamawatie; SBP Handhajani (Jurnal Akuntansi Indonesia, 2015)
Management information system of assets, or MISA, broadly refers to a system that provides to a principal of vocational high school with the tools to organize, evaluate and efficiently manage assets within a school. The purpose of this study is to describe the effectiveness of MISA in vocational high school.The data have collected through primary and secondary data. This study used a descriptive analysis method. The selected the object of this study are 3 (three) public vocational high school. The author obtained information about the MISA functions by analyzing written documents and a brief interview with the principal and MISA officer.The discussion of the paper includes: (a) the profile and structure of the organization, (b) MISA, (c) the IT structure and its effectiveness.The results showed the MISA at the vocational high school implementation has not done well. MISA should be carrying out an asset effectively on any particular subsystem on the maintenance concerning the technical guidelines asset management area.